Comparison of the Efficacies of Sacrospinous Ligament Fixation and Laparoscopic Lateral Suspension in the Treatment of Apical Prolapse: 24-Month Follow-Up Results - Engin Yurtcu; Betul Keyif; Burcu Sarigedik; Alper Basbug; Andrea Tinelli (Clinical and Experimental Obstetrics & Gynecology)
Background: Pelvic organ prolapse (POP) significantly impacts the quality of life, particularly in older women with a history of vaginal deliveries. Although conservative treatments provide some symptom relief, surgical interventions are more effective for managing POP. This study compares the outcomes and effectiveness of sacrospinous ligament fixation (SSLF) and laparoscopic lateral suspension (LLS) surgeries in the treatment of POP. Methods: This retrospective comparative cohort study included patients with symptomatic stage 2 or higher apical POP, treated at a tertiary hospital in Turkey between April 2021 and June 2022. Patients were treated with either SSLF or LLS surgeries and underwent preoperative and postoperative evaluations using the Prolapse Quality of Life (P-QoL) questionnaire and the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12). Patients were divided into two groups: SSLF (n = 47) and LLS (n = 44). The primary outcome was the rate of anatomical failure, while secondary outcomes included improvements in functional capability and quality of life. Results: The study found that the rate of postoperative anterior compartment failure was significantly lower in the LLS group compared to the SSLF group (p = 0.005). The success rate of LLS for apical prolapse was 100%, compared to 93.6% for SSLF. In the posterior compartment, SSLF demonstrated a higher success rate (86.2%) than LLS (68.5%). Both procedures improved P-QoL scores and the PISQ-12 subscales; however, a significant improvement in total PISQ-12 scores was observed only in the LLS group (p = 0.009). Conclusions: Both SSLF and LLS are effective in treating POP and enhancing quality of life. However, LLS demonstrated higher success rates for anterior and apical prolapse, while SSLF was more effective in addressing in posterior compartment defects.